PEMODELAN ARIMAX KASUS COVID-19 DIKAITKAN DENGAN CURAH HUJAN DI KOTA MAKASSAR - Sukarna Sukarna; Sahlan Sidjara; Aswi Aswi; Oktaviana Oktaviana (Math Program, Math and Science faculty, Pamulang University, 2022)
ABSTRACT This research applies a quantitative modelling approach and focuses on ARIMAX modelling in the Covid-19 case associated with rainfall in Makassar City. Data were obtained from the government's official website for daily confirmed case data of Covid-19 and rainfall (from June 25, 2020 to January 15, 2022). Rainfall is measured in mm which is the independent variable ( ), and confirmed Covid-19 as the dependent variable ( ). This research objective is to obtain the best ARIMAX model that informs the effect of rainfall intensity ( ) on the number of confirmed cases of Covid-19 ( ). This best model used the criteria that all parameters are significant, the residuals involved the white noise assumption and the best criteria measured from the smallest value of Akaike Information Criterion (AIC). The best model in this study is ARIMAX(3,0,5), with the smallest AIC value of 7,220,96. The results of this study indicate that rainfall ( ) has no significant effect on the number of confirmed Covid-19 ( ) in Makassar City. Keywords: ARIMAX, Covid-19, rainfall, Makassar. ABSTRAK Penelitian ini menerapkan pendekatan pemodelan kuantitatif (quantitative modelling approach) dan membahas pemodelan ARIMAX pada kasus Covid-19 dikaitkan dengan curan hujan di Kota Makassar. Data diperoleh dari website resmi pemerintah untuk data kasus terkonfirmasi harian Covid-19 dan juga curah hujan (mulai Tanggal 25 Juni 2020 s/d 15 Januari 2022). Curah Hujan diukur dalam mm yang merupakan variabel bebas ( , dan terkonfirmasi Covid-19 sebagai variabel terikat ( . Penelitian ini bertujuan untuk mendapatkan model ARIMAX terbaik yang menginformasikan pengaruh intensitas curah hujan ( terhadap jumlah kasus terkonfirmasi Covid-19 ( . Model terbaik ini memenuhi kriteria bahwa semua parameter signifikan, residual memenuhi asumsi white noise dan kriteria terbaiknya menggunakan nilai Akaike Information Criterion (AIC). Model terbaik yang diperoleh dalam penelitian ini adalah ARIMAX(3,0,5), dengan nilai AIC terkecil sebesar 7.220,96. Hasil penelitian ini menunjukkan bahwa Curah Hujan ( tidak berpengaruh signifikan terhadap jumlah terkonfirmasi Covid-19 ( di Kota Makassar. Kata kunci: ARIMAX, Covid-19, Curah hujan, Makassar